Development of a Measurement Method for the Classification and Performance Evaluation of Positive Pressure Ventilation (PPV) Fans - Fritsche, Manuel; Epple, Philipp; Delgado, Antonio (Proceedings of the ASME 2018 5th Joint US-European Fluids Engineering Division Summer Meeting. Volume 3: Fluid Machinery; Erosion, Slurry, Sedimentation; Experimental, Multiscale, and Numerical Methods for Multiphase Flows; Gas-Liquid, Gas-Solid, and Liquid-Solid Flows; Performance of Multiphase Flow Systems; Micro/Nano-Fluidics., 2018)
Positive Pressure Ventilation (PPV) fans are used by fire departments. The specified performance data differ depending on the manufacturer, as there is no international and commonly accepted standardized measuring method for evaluating the PPV fan performance. In the present work a new measurement method for the classification and performance evaluation of PPV fans is proposed. These fundamental investigations are based on numerical simulations and experimental test studies. The simulations have been performed with the commercial CFD software ANSYS CFX and the test measurements have been carried out on a newly developed test rig. For the predesign of the measurement method, the flow behavior of a free jet with swirl has been investigated with CFD simulations. A special feature of the PPV fans is that the generated flow rate is not only due to the flow through the rotating impeller, but also a significant flow rate is generated outside the PPV fan due to the viscous shear stresses (principle of a viscous jet pump). For the measurements a new test rig has been designed in order to measure the flow velocity of the PPV fan as it is in real firefighter’s fire combat situations. The new test rig design concept and the numerical and experimental results of these studies are presented in detail in this work.
Keywords: Fans; Performance evaluation; Pressure; Ventilation; Flow (Dynamics); Computational fluid dynamics; Engineering simulation; Impellers; Jet pumps; Shear stress; Warfare